The performance and impact of stock picks mentioned on 'mad money' - Lim, B.; Rosário, J. (Applied Financial Economics, 2010)
We analyse both the market reaction and the long-term returns of stock picks mentioned on the Consumer News and Business Channel (CNBC) programme 'Mad Money', hosted by former hedge fund manager Jim Cramer. We find that Cramer's stock-picking style is consistent with a positive-feedback trading strategy, favouring stocks which have outperformed over an interval prior to the pick date. Subsequent to a pick, Cramer's immediate effect on a stock appears inversely proportional to the corresponding firm's market capitalization. The returns over a 6-month horizon provide some evidence in favour of Cramer's stock-picking ability. In particular, his recommendations on small-cap stocks accurately predict the long-run trends.